2021
DOI: 10.1111/maq.12639
|View full text |Cite
|
Sign up to set email alerts
|

Like a Grinding Stone: How Crowdfunding Platforms Create, Perpetuate, and Value Health Inequities

Abstract: This article explores how inequities are reproduced by, and valued within, the increasingly ubiquitous world of medical crowdfunding. As patients use platforms like GoFundMe to solicit donations for health care, success stories inundate social media. But most crowdfunders experience steep odds and marginal benefits. Drawing on the problematic figure of the "black box" in health disparities research and technology studies, I offer ethnography as a tool for unpacking often inscrutable and complex pathways throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…We prioritised thematic analysis of a large number of pages over, for example, pursuing qualitative interviews with a sample of page creators. Crowdfunding studies have demonstrated that interviews add depth and context to the stories presented on fundraising pages ( Kenworthy, 2021 ; Kerr et al, 2021 ). However the NHS COVID-19 appeal is distinct from personal crowdfunders where intimate details of people's lives are shared ( Berliner and Kenworthy, 2017 ; Kerr et al, 2021 ).…”
Section: Methods and Datamentioning
confidence: 99%
See 4 more Smart Citations
“…We prioritised thematic analysis of a large number of pages over, for example, pursuing qualitative interviews with a sample of page creators. Crowdfunding studies have demonstrated that interviews add depth and context to the stories presented on fundraising pages ( Kenworthy, 2021 ; Kerr et al, 2021 ). However the NHS COVID-19 appeal is distinct from personal crowdfunders where intimate details of people's lives are shared ( Berliner and Kenworthy, 2017 ; Kerr et al, 2021 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…Sociological analyses of crowdfunding for individual healthcare needs has focused on the dynamics of fundraising as a social practice. Fundraising platforms are interpreted as stages on which illness narratives are performed, specifically combined within narratives of the individual's good character and worthiness ( Berliner and Kenworthy, 2017 ; Kenworthy, 2021 ; Paulus and Roberts, 2018 ). Discursive strategies to promote the deservingness of a cause ( Kerr et al, 2021 ) can create a burden on already sick individuals, who are required to prove their legitimacy and their gratitude ( Kenworthy, 2021 ; Kerr et al, 2021 ).…”
Section: Background: Crowdfunding Charity and The Nhsmentioning
confidence: 99%
See 3 more Smart Citations